Managing Character Education in Early Childhood: A Multisite Case Study of Planning, Leadership, and Supervision Practices - Muhammad Sidik; Amiruddin Siahaan; Yusuf Hadijaya (AL-ISHLAH: Jurnal Pendidikan, 2026)
Character education in early childhood requires a comprehensive managerial framework that extends beyond classroom practices. However, many institutions face challenges in implementing systematic and integrated management approaches. This study examines and compares the management of character education in two early childhood institutions, focusing on how planning, organizing, implementation, and supervision shape program effectiveness. A qualitative multi-site case study was conducted at PAUD Az Zikro and PAUD Al-Maghfiroh. Data were collected through in-depth interviews, participant observation, and document analysis. The analysis followed Miles and Huberman’s interactive model, complemented by cross-case comparison to identify patterns and differences between institutions. Both institutions are grounded in religious-based character values but differ substantially in managerial practices. PAUD Az Zikro employs a simple organizational structure, administratively oriented supervision, and non-standardized implementation. In contrast, PAUD Al-Maghfiroh adopts data-driven planning, distributed leadership, structured learning strategies, measurable indicators, and instrument-based supervision. These differences influence the coherence, accountability, and sustainability of character education programs. The findings underscore the critical role of integrated management in ensuring effective character education. A systematic alignment of planning, organizing, implementation, and supervision enhances program consistency and institutional resilience. The study contributes theoretically by extending character education discourse from a value-internalization perspective to a management-based model, where managerial components function as interrelated systems mediating character development. Effective character education is thus contingent upon participatory planning, collaborative organizational structures, authentic assessment, and reflective supervision. Future research should explore broader multisite contexts, longitudinal designs, and the use of digital or AI-assisted tools to strengthen supervision and assessment practices.